Characterizing synthesis-dependent microhomology-mediated end-joining requirements through signatures of inaccurate double strand break repair - Hanscom, Terrence. (Tufts University. Tisch Library., 2021)
Thesis (Ph.D.)--Tufts University, 2021.; Submitted to the Dept. of Biology.; Advisor: Mitch McVey.; Committee: Catherine Freudenreich, Sergei Mirkin, and Jeremy Stark.; Keyword: Molecular biology.